Caller resistance to perform cardio-pulmonary resuscitation in emergency calls for cardiac arrest. (July 2020) - Riou, Marine; Ball, Stephen; Whiteside, Austin; Gallant, Sheryl; Morgan, Alani; Bailey, Paul; Finn, Judith
Abstract: A key objective of an emergency call for cardiac arrest is to recruit a bystander to perform cardio-pulmonary resuscitation (CPR) until the ambulance arrives. Emergency medical services worldwide work towards increasing the rate of bystander-CPR, and existing research has identified a number of physical barriers to the provision of bystander-CPR. Yet, little is known about the specific ways in which emergency callers resist recruitment to perform basic first-aid, sometimes in the absence of any physical obstacle. This study investigated 65 emergency calls for cardiac arrest received in Australia in 2014 and 2015, in which the callers initially resisted CPR. We used conversation analysis to examine callers' practices to resist recruitment and call-takers' practices to counter this resistance. We found that callers who resisted CPR typically provided an account. When callers accounted for their resistance on deontic grounds, they expressed that CPR was not a possible course of action (e.g. "I can't do it"). When callers provided an epistemic account, their justification was based on their knowledge or opinion (e.g. "I think it's too late"). Our findings suggest that epistemic resistance can be a barrier to bystander-CPR. We identified two practices used by call-takers to address caller resistance based on epistemics. Providing more context on the purpose of CPR (e.g. "this is to help him in the meantime") seemed effective in persuading callers to perform CPR. By contrast, aligning with the caller's epistemic and deontic rights (e.g. "it's up to you") did not seem effective in persuading callers. Highlights: Emergency callers account for their resistance to provide first aid to patients. Saying that the patient is already dead is a common justification for resisting CPR. Callers can be persuaded when provided with more context on CPR. Conversation Analysis can identify strategies to overcome barriers to CPR.